An electronic framework to enhance conceptual learning. (1st January 2011) - Bregman, Robert L.
Almost all courses use homework assignments as a means to help students improve their mastery of concepts introduced in class. The development of the assignments, checking of solutions and delivery of feedback to students can be time-consuming and resource-intensive. This research introduces a simple framework that has been used to develop fully automated electronic assignments covering various concepts in operations management (OM). The resultant assignments can be run over the internet or directly on student computers. Student feedback based on survey responses and usage data suggests that they view the assignments as an important component of the course. The framework, which can be used to deliver assignments covering different concepts from other functional areas, and the completed assignments for OM are provided free for non-profit, educational use.